Stem cell-derived exosome delivery systems for treating atherosclerosis: The new frontier of stem cell therapy - Hassan Tariq; Syeda Zunaira Bukhari; Ruibing An; Jian Dong; Ayesha Ihsan; Muhammad Rizwan Younis (Materials Today Bio)
Cardiovascular diseases (CVDs) are a leading cause of mortality worldwide. As a chronic inflammatory disease with a complicated pathophysiology marked by abnormal lipid metabolism and arterial plaque formation, atherosclerosis is a major contributor to CVDs and can induce abrupt cardiac events. The discovery of exosomes' role in intercellular communication has sparked a great deal of interest in them recently. Exosomes are involved in strategic phases of the onset and development of atherosclerosis because they have been identified to control pathophysiologic pathways including inflammation, angiogenesis, or senescence. This review investigates the potential role of stem cell-derived exosomes in atherosclerosis management. We briefly introduced atherosclerosis and stem cell therapy including stem cell-derived exosomes. The biogenesis of exosomes along with their secretion and isolation have been elaborated. The design engineering of exosomes has been summarized to present how drug loading and surface modification with targeting ligands can improve the therapeutic and targeting capacity of exosomes, demonstrating atheroprotective action. Moreover, the mechanism of action (endothelial dysfunction, reduction of dyslipidemia, macrophage polarization, vascular calcification, and angiogenesis) of drug-loaded exosomes to treat atherosclerosis has been discussed in detail. In the end, a comparative and balanced viewpoint has been given regarding the current challenges and potential solutions to advance exosome engineering for cardiovascular therapeutic applications.